Strategi Multilanguage untuk Pembelajaran Bahasa Arab: Studi di Ma‘had Mahasiswa UIN Maulana Malik Ibrahim, Malang - Nuril Mufidah; Nihayatus Sa'adah; Nur Kholis (Universitas Negeri Jakarta, 2019)
This study aims to determine the effect of learning Arabic using a multilanguage strategy in Ma‘had. The study is qualitative research, taking the students (mahasantri) Ma‘had Universitas Islam Negeri Maulana (UIN) Maulana Malik Ibrahim, Malang, in 2016. The method of data collection in this study was carried out by observation, interviews, and documentation. The results of the study show that with the use of the Multilanguage strategy, learning can attract motivation and interest in students who do not have an adequate language background because Indonesian helps to bring students into a foreign language with a purpose, especially Arabic. Also, the use of this strategy allows students to be able to use more than one language.